Pengaruh Penggunaan Media Board Game Monopoli terhadap Peningkatan Pemahaman Materi Norma pada Siswa Kelas V SDN 1 Cengal - Eliza; Agus Saeful Anwar; Nurholifah; Ismawati (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
Norms are one of the essential topics in Pancasila Education, as they help students develop responsible attitudes and appropriate behavior in their daily lives. However, conventional teaching methods often make it difficult for students to understand and apply the concept of norms effectively. Therefore, the purpose of this study was to examine the effect of using Monopoly board game media on fifth-grade students' understanding of norms at Cengal 1 Public Elementary School. This study employed a quantitative approach using a quasi-experimental method with an unequal control group design. The population consisted of 59 fifth-grade students, comprising 33 students in the experimental class and 26 students in the control class. Data were collected through pre-tests and post-tests. The data were analyzed using SPSS version 27, including normality, homogeneity, independent samples t-test, and N-Gain analyses. The results showed that the experimental class achieved a higher average post-test score (82.30) than the control class (69.85). Furthermore, the independent samples t-test yielded a significance value (Sig. 2-tailed) of 0.000 (< 0.05), indicating that the use of Monopoly board game media had a significant effect on improving students' understanding of norms. The N-Gain analysis revealed that the experimental class obtained an average N-Gain score of 71.20%, which was categorized as moderately effective, whereas the control class achieved an average score of 51.82%, categorized as less effective. Therefore, the Monopoly board game media was proven to be effective in enhancing students' understanding of norms and can serve as a creative and engaging learning medium for Pancasila Education in elementary schools.